The path to developing realistic finite element long bone models. (1st January 2012) - Au, Anthony G.; Amirfazli, A.
Current computational capabilities allow for rapid construction of finite element (FE) models but do not guarantee representative models. Simplifications to FE models are necessary because of computational limitations and scarcity of physiological data. With proper modelling and validation, FE models can progress from the realm of parametric studies to clinical applicability. It is often unclear, in the preliminary stages of FE model development, what simplifications are suitable without sacrificing solution accuracy and clinical relevance. This paper presents a technique to create proper FE long bone models for those wanting to develop their own studies. It highlights four important parameters (geometry, material properties, loading conditions, validation) that must be carefully considered and presents a number of methods to aid in achieving proper representation of each parameter. Knee bones are used as an example but the technique can be extended to reconstruct different long bones in the human body with some adjustments.